Renewable Energy Use in Agriculture in Iran - Fami, Hossein Shabanali; Khodabakhshi, Azadeh; Atashi, Mhtab Pour; Ghasemi, Javad; Ahmadi, Fatemeh (Annals of Arid Zone, 2016)
Agriculture is one of the most important economic sectors of Iran in which both renewable and non-renewable energies are major input for any farming operation. In fact, the relation between agriculture and energy is very close. For many years, the country has used :enewable energy in agriculture and allied activities and acquired experiences with ind;genous technologies in using renewable energy for agricultural purposes. Since, introduction of fossil fuel its use in agricultural operations increased, which increased the socio-environmental cost of farming in Iran. There is a need to revisit this area and revitalize the use of these safe renewable energy sources. The country attempts to develop plans for use of renewable energy in agriculture so that sustainable farming goals are rapidly achieved. Key words: Renewable energy, agriculture, sust’:linable, Iran.